Negative electrode for lithium metal secondary battery, manufacturing method thereof, and lithium metal secondary battery

The negative electrode with an uneven lithium layer and antioxidant coating addresses oxidation issues, enhancing discharge capacity, rate characteristics, and cycle characteristics in lithium metal secondary batteries by stabilizing the lithium layer and improving reaction efficiency.

JP2025005961APending Publication Date: 2025-01-17HONDA MOTOR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023106437
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Lithium metal secondary batteries face challenges in improving discharge capacity, rate characteristics, and cycle characteristics due to the oxidation of the lithium layer, which increases surface resistance and deteriorates performance.

Method used

A negative electrode for lithium metal secondary batteries is developed with a lithium-containing metal layer having an uneven surface and coated with an antioxidant film, featuring a developed area ratio of 1.0 or more, an arithmetic mean roughness of 0.5 μm or more, and an antioxidant coating containing oxygen and carbon, with an O/C molar ratio of 3 to 5 and a thickness of 50 nm or more, to enhance stability and reaction area.

Benefits of technology

The solution results in a lithium metal secondary battery with improved discharge capacity, rate characteristics, and cycle characteristics by preventing oxidation and ensuring uniform lithium deposition and dissolution, maintaining chemical stability and electrical stability over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005961000001_ABST
    Figure 2025005961000001_ABST
Patent Text Reader

Abstract

To provide a negative electrode for a lithium metal secondary battery, which has a wide reaction area and is chemically stable, and a manufacturing method thereof.SOLUTION: A negative electrode 20 for a lithium metal secondary battery includes a negative electrode current collector 21 and a lithium-containing metal layer disposed on at least one surface of the negative electrode current collector 21, at least a part of the surface of the lithium-containing metal layer 22 has an uneven shape, the developed area ratio Sdr of the surface is 1.0 or more, and the surface is covered with an antioxidant coating.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a lithium metal secondary battery, a method for producing the same, and a lithium metal secondary battery. [Background technology]

[0002] In recent years, research and development of secondary batteries that contribute to energy efficiency has been conducted to ensure that many people have access to affordable, reliable, sustainable and advanced energy. Lithium metal secondary batteries, which use lithium metal as the negative electrode active material, have attracted attention as a type of secondary battery due to their high energy density.

[0003] As the negative electrode of a lithium metal secondary battery, a laminated negative electrode having a negative electrode current collector and a lithium layer disposed on at least one surface of the negative electrode current collector is known. In this laminated negative electrode, it has been considered to provide irregularities on the surface of the lithium layer (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-272726 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the lithium metal secondary battery has a problem in improving the discharge capacity, rate characteristics, and cycle characteristics. In order to improve the discharge capacity and rate characteristics of the lithium metal secondary battery, it is effective to increase the surface area of ​​the lithium layer of the negative electrode to increase the reaction area of ​​the negative electrode. However, when the surface area of ​​the lithium layer of the negative electrode is increased, the lithium layer is easily oxidized. When the lithium layer is oxidized, the surface resistance of the lithium layer increases, and there is a risk that the characteristics such as the discharge capacity, rate characteristics, and cycle characteristics will decrease.

[0006] The present application aims to provide a negative electrode for a lithium metal secondary battery that has a large reaction area and is chemically stable, a method for producing the same, and a lithium metal secondary battery that has improved discharge capacity, rate characteristics, and cycle characteristics, thereby contributing to energy efficiency. [Means for solving the problem]

[0007] The present inventors have found that, in order to solve the above problems, it is effective to increase the surface area of ​​the lithium metal layer by making the surface of the lithium metal layer uneven and at the same time coat the surface of the lithium metal layer with an oxidation-resistant coating, and have thus completed the present invention.

[0008] (1) A negative electrode for a lithium metal secondary battery, comprising: a negative electrode current collector; and a lithium-containing metal layer disposed on at least one surface of the negative electrode current collector, at least a portion of the surface of the lithium-containing metal layer having an uneven shape, a developed area ratio Sdr of the surface being 1.0 or more, and the surface being covered with an antioxidant coating.

[0009] According to the negative electrode for lithium metal secondary battery of (1), at least a part of the surface of the lithium-containing metal layer has an uneven shape and the developed area ratio Sdr is 1.0 or more, so that the surface area, i.e., the reaction area, of the lithium-containing metal layer is large. In addition, at least a part of the surface of the lithium-containing metal layer is covered with an oxidation-resistant coating, so that the lithium-containing metal layer is resistant to oxidation and is chemically stable.

[0010] (2) The negative electrode for a lithium metal secondary battery according to (1), wherein the arithmetic mean roughness Sa of the surface of the lithium-containing metal layer is 0.5 μm or more.

[0011] According to the negative electrode for lithium metal secondary batteries of (2), the arithmetic mean roughness Sa of the surface having a concave and convex shape is large, so that the reaction area of ​​the lithium-containing metal layer is certainly wide. By increasing the arithmetic mean roughness Sa of the negative electrode for lithium metal secondary batteries, the contact angle with the electrolyte is reduced, and the wettability of the electrolyte is improved.

[0012] (3) The negative electrode for a lithium metal secondary battery according to (1) or (2), wherein the antioxidant coating contains oxygen and carbon, and an average content of the oxygen relative to an average content of the carbon within a range from the surface of the antioxidant coating to a depth of 50 nm is in a molar ratio of 3 or more and 5 or less.

[0013] According to the negative electrode for lithium metal secondary batteries (3), the antioxidant coating contains 3 to 5 moles of oxygen (O) per mole of carbon (C), and carbon and oxygen form carbonate, so that the coating is chemically stable. In addition, the antioxidant coating has a thickness of 50 nm or more, so that the antioxidant ability is high. As a result, the surface of the lithium-containing metal layer is less susceptible to oxidation, and is more chemically stable.

[0014] (4) The negative electrode for a lithium metal secondary battery according to any one of (1) to (3), wherein the antioxidant coating contains lithium carbonate.

[0015] According to the negative electrode for a lithium metal secondary battery of (4), the antioxidant coating contains lithium carbonate, which makes the negative electrode more chemically stable.

[0016] (5) The negative electrode for a lithium metal secondary battery according to any one of (1) to (4), wherein the lithium-containing metal layer has a silicon content of 400 mass ppm or less relative to the lithium content in terms of mass ratio.

[0017] (5) The negative electrode for lithium metal secondary batteries has a low silicon content, so that it is highly stable and is less susceptible to change over time.

[0018] (6) The negative electrode for a lithium metal secondary battery according to any one of (1) to (5), wherein a peel strength between the negative electrode current collector and the lithium-containing metal layer is 100 N / cm or more.

[0019] According to the negative electrode for a lithium metal secondary battery of (6), the peel strength between the negative electrode current collector and the lithium-containing metal layer is high, so that the electrical characteristics are stable for a long period of time.

[0020] (7) A lithium metal secondary battery comprising the negative electrode for lithium metal secondary batteries according to any one of (1) to (6) above.

[0021] According to the lithium metal secondary battery (7), since it has the above-mentioned negative electrode for lithium metal secondary batteries, the discharge capacity, rate characteristics and cycle characteristics are improved.

[0022] (8) A method for producing a negative electrode for a lithium metal secondary battery, comprising: a preparation step of preparing a laminate having a negative electrode current collector and a lithium-containing metal layer disposed on at least one surface of the negative electrode current collector; and a concavo-convex transfer step of pressing a concavo-convex transfer material having a concavo-convex portion with an arithmetic mean roughness Sa of 0.5 μm or more and a developed area ratio Sdr of 1.0 or more against a surface of the laminate facing the lithium-containing metal layer.

[0023] According to the method for producing a negative electrode for a lithium metal secondary battery (8), in the unevenness transfer step, a unevenness transfer material having an uneven portion with a large development area ratio Sdr is pressed against the lithium-containing metal layer, so that an uneven shape can be stably formed on the surface of the lithium-containing metal layer.

[0024] (9) The method for producing a negative electrode for a lithium metal secondary battery according to (8), wherein in the unevenness transfer step, a solvent having an ether bond or a carbonate bond is interposed between the surface of the laminate on the lithium-containing metal layer side and the unevenness transfer material.

[0025] According to the method for producing a negative electrode for a lithium metal secondary battery of (9), since a solvent is interposed between the lithium-containing metal layer and the unevenness transfer material, the lithium-containing metal layer and the unevenness transfer material can be easily peeled off. In addition, since the solvent has an ether bond or a carbonate ester bond, when new lithium metal is exposed by pressing the unevenness transfer material against the lithium-containing metal layer, the lithium metal and the solvent react to generate lithium carbonate. Therefore, an oxidation prevention coating can be stably formed on the surface of the lithium-containing metal layer.

[0026] (10) The method for producing a negative electrode for a lithium metal secondary battery according to (8) or (9), wherein the surface of the unevenness transfer material has an arithmetic mean roughness Sa of 0.5 μm or more.

[0027] According to the method for producing a negative electrode for a lithium metal secondary battery (10), since the arithmetic mean roughness Sa of the surface of the unevenness transfer material used in the unevenness transfer step is large, an uneven shape can be more stably formed on the surface of the lithium-containing metal layer. Effect of the Invention

[0028] According to the present invention, it is possible to provide a negative electrode for a lithium metal secondary battery that has a large reaction area and is chemically stable, and a method for producing the same. Also, according to the present invention, it is possible to provide a lithium metal secondary battery that has improved discharge capacity, rate characteristics, and cycle characteristics. [Brief description of the drawings]

[0029] [Figure 1] 1 is a cross-sectional view showing a lithium metal secondary battery according to one embodiment of the present invention. [Diagram 2] 1 is a cross-sectional SEM photograph of a negative electrode for a lithium metal secondary battery according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a lithium metal secondary battery negative electrode manufacturing apparatus that can be used in a method for manufacturing a lithium metal secondary battery negative electrode according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.

[0031] Fig. 1 is a cross-sectional view showing a lithium metal secondary battery according to one embodiment of the present invention, and Fig. 2 is a cross-sectional SEM photograph of a negative electrode for a lithium metal secondary battery according to one embodiment of the present invention. 1, a lithium metal secondary battery 10 includes an electrode stack in which a negative electrode 20, a separator 30, and a positive electrode 40 are stacked in this order. The electrode stack is housed in an exterior body (not shown) together with an electrolyte (not shown).

[0032] The negative electrode 20 has a negative electrode current collector 21 and a lithium-containing metal layer 22 disposed on at least one surface of the negative electrode current collector 21 .

[0033] The negative electrode current collector 21 is not particularly limited as long as it has a function of collecting current from the negative electrode 20, and a material used as a negative electrode current collector for a general lithium metal secondary battery can be used. Examples of the material of the negative electrode current collector 21 include copper (Cu), stainless steel (SUS), nickel (Ni), and the like. Examples of the shape of the negative electrode current collector 21 include a foil shape, a plate shape, and the like. When the negative electrode current collector 21 is a foil shape, the thickness of the negative electrode current collector 21 may be in the range of 5.0 μm or more and 50.0 μm or less. The arithmetic mean roughness Sa of the negative electrode current collector 21 on the lithium-containing metal layer 22 side may be, for example, in the range of 0.2 μm or more and 2.0 μm or less. The maximum height Sz of the negative electrode current collector 21 on the lithium-containing metal layer 22 side may be, for example, 1 / 3 or more of the thickness, or may be in the range of 5.0 μm or more and 20.0 μm or less.

[0034] The lithium-containing metal layer 22 has a function of depositing lithium ions transferred from the positive electrode 40 on the surface of the negative electrode 20 during charging of the lithium metal secondary battery 10, thereby facilitating the generation of a lithium metal layer. During discharging of the lithium metal secondary battery 10, the lithium of the lithium metal layer deposited on the surface of the negative electrode 20 dissolves in the electrolyte. As shown in FIG. 2, at least a part of the surface of the lithium-containing metal layer 22 opposite to the negative electrode current collector 21 has an uneven shape, and the developed area ratio Sdr of the surface is set to 1.0 or more. The thickness of the lithium-containing metal layer 22 may be, for example, in the range of 5 μm or more and 50 μm or less. The developed area ratio Sdr of the uneven surface of the lithium-containing metal layer 22 may be, for example, in the range of 1.1 or more and 3.0 or less. The arithmetic mean roughness Sa of the uneven surface of the lithium-containing metal layer 22 may be, for example, 0.5 μm or more, or may be in the range of 1.0 μm or more and 2.0 μm or less. The maximum height Sz of the uneven surface of the lithium-containing metal layer 22 may be, for example, 1 / 3 or more of the thickness, or may be in the range of 10.0 μm or more and 25.0 μm or less. The developed area ratio Sdr, the arithmetic mean roughness Sa, and the maximum height Sz can be measured using a commercially available laser microscope.

[0035] The lithium-containing metal layer 22 is covered with an anti-oxidation coating (not shown). The anti-oxidation coating prevents oxidation of the lithium-containing metal layer 22. This makes it difficult for the lithium metal secondary battery 10 to oxidize even when the battery 10 is repeatedly charged and discharged.

[0036] The oxidation-resistant coating may contain oxygen (O) and carbon (C), or may contain lithium carbonate. The molar ratio (O / C molar ratio) of the average content of oxygen (O) to the average content of carbon (C) within a range from the surface of the oxidation-resistant coating (the surface of the lithium-containing metal layer 22) to a depth of 50 nm may be 3 or more and 5 or less. The O / C molar ratio being within the above range indicates that the oxidation-resistant coating contains carbonate and has a thickness of 50 nm or more. The O / C molar ratio can be confirmed, for example, by using XPS (X-ray photoelectron spectroscopy).

[0037] The lithium-containing metal layer 22 contains lithium or a lithium alloy. The lithium alloy contains a metal that forms an alloy with lithium. Examples of metals that form an alloy with lithium include Mg, Au, Ag, In, Ge, Sn, Pb, Al, and Zn. The lithium-containing metal layer 22 may contain inevitable impurities. The inevitable impurities are substances that are inevitably mixed in the raw materials or the manufacturing process. An example of the inevitable impurity is silicon. The mass ratio of the silicon content to the lithium content (Si / Li mass ratio) may be, for example, 400 ppm by mass or less.

[0038] The negative electrode current collector 21 and the lithium-containing metal layer 22 may be joined with strong adhesion. The peel strength between the negative electrode current collector 21 and the lithium-containing metal layer 22 may be, for example, 100 N / cm or more, or 200 N / cm or more.

[0039] The separator 30 is not particularly limited as long as it prevents contact between the negative electrode 20 and the positive electrode 40 and allows lithium ions to pass through, and any separator used in a general lithium metal secondary battery can be used. For example, a porous sheet or a nonwoven sheet can be used as the separator 30. Examples of materials for the porous sheet include polyolefins such as polyethylene and polypropylene, aramid, polyimide, and fluororesin. Examples of materials for the nonwoven sheet include glass fiber and cellulose fiber. The surface of the separator 30 facing the positive electrode 40 may be ceramic-coated. Examples of materials for the ceramic coating include aluminum oxide (Al2O3) and silicon oxide (SiO2). The thickness of the ceramic coating may be, for example, in the range of 2.0 μm or more and 5.0 μm or less. When the thickness of the ceramic coating is within the above range, the thermal stability of the separator 30 can be improved while suppressing an increase in the internal resistance value due to an increase in the thickness of the separator 30.

[0040] The positive electrode 40 includes a positive electrode current collector 41 and a positive electrode active material layer 42 disposed on the surface of the positive electrode current collector 41 facing the separator 30 .

[0041] The positive electrode current collector 41 is not particularly limited as long as it has a function of collecting current from the positive electrode 40, and may be any positive electrode current collector used in general lithium metal secondary batteries. Examples of materials for the positive electrode current collector 41 include aluminum, aluminum alloy, stainless steel, nickel, iron, and titanium. Examples of the shape of the positive electrode current collector 41 include a foil shape, a plate shape, and the like.

[0042] The positive electrode active material layer 42 contains at least one type of positive electrode active material. There are no particular limitations on the positive electrode active material, and any material that is used in the positive electrode layer of a typical lithium metal secondary battery can be used. As the positive electrode active material, for example, a layered active material containing lithium, a spinel type active material, an olivine type active material, or the like can be used. Specific examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2(p+q+r=1), lithium manganese oxide (LiMn2O4), Li 1+x Mn 2-x-y Examples of such materials include Li-Mn spinel substituted with different elements represented by MO4 (x+y=2, M=at least one selected from Al, Mg, Co, Fe, Ni, and Zn), lithium titanate (oxide containing Li and Ti), and lithium metal phosphate (LiMPO4, M=at least one selected from Fe, Mn, Co, and Ni).

[0043] The positive electrode active material layer 42 may optionally contain a conductive assistant to improve conductivity. In addition, from the viewpoint of expressing flexibility, etc., the positive electrode active material layer 42 may optionally contain a binder. There are no particular limitations on the conductive assistant and binder, and those used in the positive electrode layer of a general lithium metal secondary battery may be used.

[0044] The electrolytic solution includes an organic solvent and an electrolyte. Examples of the organic solvent include cyclic carbonates, chain carbonates, cyclic ethers, chain ethers, hydrofluoroethers, aromatic ethers, sulfones, cyclic esters, chain carboxylates, and nitriles. Examples of the cyclic carbonates include ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate. Examples of the chain carbonates include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of the cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, and 4-methyl1,3-dioxolane. Examples of the chain ethers include 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, and diethyl ether. Examples of hydrofluoroethers include 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl)ether, 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane, and the like. Examples of aromatic ethers include anisole. Examples of sulfones include sulfolane and methylsulfolane. Examples of cyclic esters include γ-butyrolactone, and the like. Examples of chain carboxylates include acetates, butyrates, and propionates. Examples of nitriles include acetonitrile and propionitrile. The organic solvents may be used alone or in combination of two or more.

[0045] The electrolyte is a source of lithium ions, which are charge transfer media, and contains a lithium salt. Examples of the lithium salt include LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(CF3SO2)3, LiN(CF3SO2)2(LiTFSI), LiN(FSO2)2(LiFSI), and LiBC4O8. The lithium salt may be used alone or in combination of two or more. The concentration of the electrolyte is, for example, within the range of 1.5 to 4.0 mol / L.

[0046] According to the lithium metal secondary battery 10 of the present embodiment configured as described above, at least a part of the surface of the lithium-containing metal layer 22 of the negative electrode 20 has an uneven shape, the development area ratio Sdr is 1.0 or more, and the surface area, i.e., the reaction area, of the lithium-containing metal layer 22 is large. In addition, since at least a part of the surface of the lithium-containing metal layer 22 is covered with an oxidation-resistant coating, the lithium-containing metal layer 22 is less likely to oxidize and is chemically stable. Therefore, in the lithium metal secondary battery 10, lithium is more likely to deposit uniformly on the surface of the lithium-containing metal layer 22 during charging, and the deposited lithium is more likely to dissolve uniformly during discharging. Therefore, the lithium metal secondary battery 10 has improved discharge capacity, rate characteristics, and cycle characteristics.

[0047] In the lithium metal secondary battery 10 of this embodiment, when the arithmetic mean roughness Sa of the lithium-containing metal layer 22 is as large as 0.5 μm or more, the reaction area of ​​the lithium-containing metal layer 22 is reliably increased, thereby improving the discharge capacity and rate characteristics of the lithium metal secondary battery 10. In addition, the larger arithmetic mean roughness Sa of the lithium metal layer 22 reduces the contact angle with the electrolyte, thereby improving the wettability of the electrolyte.

[0048] In the lithium metal secondary battery 10 of this embodiment, when the molar ratio (O / C molar ratio) of the average content of oxygen (O) to the average content of carbon (C) within a range from the surface of the antioxidant coating (the surface of the lithium-containing metal layer 22) to a depth of 50 nm is 3 or more and 5 or less, the antioxidant coating contains oxygen (O) in an amount of 3 moles or more and 5 moles or less per mole of carbon (C), and carbon and oxygen form carbonate, so that it is chemically stable. In addition, since the thickness of the antioxidant coating is 50 nm or more, the antioxidant ability is high. Therefore, the surface of the lithium-containing metal layer 22 is less likely to oxidize and is more chemically stable. Therefore, the cycle characteristics of the lithium metal secondary battery 10 are further improved. Furthermore, when the antioxidant coating contains lithium carbonate, it is even more chemically stable. Therefore, the cycle characteristics of the lithium metal secondary battery 10 are even more improved.

[0049] In the lithium metal secondary battery 10 of this embodiment, when the silicon content relative to the lithium content in the lithium-containing metal layer 22 is as low as 400 mass ppm or less in mass ratio, the stability of the lithium-containing metal layer 22 is high and the lithium-containing metal layer 22 is less likely to change over time. Therefore, the cycle characteristics of the lithium metal secondary battery 10 are further improved.

[0050] In the lithium metal secondary battery 10 of this embodiment, when the peel strength between the negative electrode current collector 21 and the lithium-containing metal layer 22 is as high as 100 N / cm or more, the electrical characteristics are stable for a long period of time, and the cycle characteristics of the lithium metal secondary battery 10 are further improved.

[0051] Next, a method for manufacturing the negative electrode 20 for a lithium metal secondary battery will be described. FIG. 3 is a schematic diagram showing a lithium metal secondary battery negative electrode manufacturing apparatus that can use the method for manufacturing a lithium metal secondary battery negative electrode according to one embodiment of the present invention. As shown in FIG. 3, the manufacturing apparatus 100 has a pair of roll presses 110 and a laminate 120 for forming unevenness. The laminate 120 for forming unevenness includes a negative electrode material laminate 20a and an unevenness transfer material 122 arranged between a pair of release plates 121. The negative electrode material laminate 20a has a negative electrode current collector 21a and a lithium-containing metal layer 22a arranged on one surface of the negative electrode current collector 21a. The unevenness transfer material 122 has an uneven portion on one surface, and is arranged so that the lithium-containing metal layer 22a and the uneven portion of the unevenness transfer material 122 are in contact with each other. The uneven portion of the unevenness transfer material 122 has a development area ratio Sdr of 1.0 or more. The developed area ratio Sdr of the uneven portion of the unevenness transfer material 122 may be within a range of 1.1 or more and 3.0 or less. The arithmetic mean roughness Sa of the uneven portion of the unevenness transfer material 122 may be, for example, 0.5 μm or more, or may be within a range of 1.0 μm or more and 2.0 μm or less. The maximum height Sz of the uneven portion of the unevenness transfer material 122 may be, for example, within a range of 5.0 μm or more and 25.0 μm or less. For example, a copper plate can be used as the release plate 121.

[0052] The negative electrode 20 for a lithium metal secondary battery can be manufactured, for example, by a method including a preparation step and a pattern transfer step.

[0053] The preparation step is a step of preparing a negative electrode material laminate 20a. The negative electrode material laminate 20a can be produced, for example, by stacking a negative electrode current collector 21a and a lithium-containing metal layer 22a and applying pressure to them.

[0054] The unevenness transfer step is a step of preparing the unevenness forming laminate 120, and pressing the unevenness forming laminate 120 using a roll press 110 to press the unevenness transfer material 122 onto the surface of the lithium-containing metal layer 22a. By pressing the unevenness transfer material 122 onto the surface of the lithium-containing metal layer 22a, the uneven shape of the uneven portion of the unevenness transfer material 122 is transferred onto the surface of the lithium-containing metal layer 22a. The conditions of the press are not particularly limited, but are conditions in which the compression ratio of the unevenness forming laminate 120 by pressing is within a range of, for example, 30% or more and 50% or less. When the compression ratio is within this range, it becomes easy to transfer the uneven shape to the surface of the lithium-containing metal layer 22a without peeling the lithium-containing metal layer 22a from the negative electrode current collector 21a. The compression ratio of the lithium-containing metal layer 22a can be adjusted by the distance between the pair of roll presses 110 (indicated by the arrow in FIG. 3).

[0055] In the unevenness transfer step, before pressing the unevenness transfer material 122 against the surface of the lithium-containing metal layer 22a, a solvent may be interposed between the lithium-containing metal layer 22a and the unevenness transfer material 122. The solvent may have an ether bond or a carbonate ester bond. For example, DME (1,2-dimethoxyethane) can be used as a solvent having an ether bond. For example, dimethyl carbonate can be used as a solvent having a carbonate ester bond.

[0056] According to the manufacturing method of the negative electrode 20 for a lithium metal secondary battery of this embodiment configured as described above, in the unevenness transfer step, the unevenness transfer material 122 having a large development area ratio Sdr is pressed against the lithium-containing metal layer 22a, so that the uneven shape can be stably formed on the surface of the lithium-containing metal layer 22.

[0057] In the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of this embodiment, when a solvent having an ether bond or a carbonate ester bond is interposed between the lithium-containing metal layer 22a and the unevenness transfer material 122, the lithium-containing metal layer 22a and the unevenness transfer material 122 after the unevenness is formed can be easily peeled off. Furthermore, since the solvent has an ether bond or a carbonate ester bond, when new lithium metal is exposed by pressing the unevenness transfer material 122 against the lithium-containing metal layer 22a, the lithium metal and the solvent react to generate lithium carbonate. Therefore, an oxidation prevention coating can be stably formed on the surface of the lithium-containing metal layer 22a after the unevenness is formed. In addition, in the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of this embodiment, when the arithmetic mean roughness Sa of the surface of the unevenness transfer material 122 is as large as 1.0 μm or more, the unevenness can be more stably formed on the surface of the lithium-containing metal layer.

[0058] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. For example, the lithium metal secondary battery 10 of the present embodiment is a non-aqueous solvent type lithium metal secondary battery containing an electrolyte, but the present invention is not limited thereto. The lithium metal secondary battery of the present invention may be a solid electrolyte type lithium metal secondary battery.

[0059] In the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of this embodiment, a solvent having an ether bond or a carbonate ester bond is interposed between the lithium-containing metal layer 22a and the unevenness transfer material 122, but the present invention is not limited thereto. However, when a solvent having no ether bond or carbonate ester bond is used, it is preferable to provide a step of forming an oxidation-resistant coating on the surface of the lithium-containing metal layer 22a after the unevenness is formed. As a method for forming the oxidation-resistant coating, for example, a method of contacting the surface of the lithium-containing metal layer 22a after the unevenness is formed with carbon dioxide gas can be used. In addition, in the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of this embodiment, a roll press 110 is used as a pressing device for the unevenness-forming laminate 120, but the pressing device is not limited thereto. EXAMPLES

[0060] In this example, a Li-Cu laminate in which Li foil is arranged on the surface of Cu foil is used as the raw material of the negative electrode. Two laminates, Li-Cu laminates 1 and 2, were used as the Li-Cu laminate. The thickness of the Cu foil, arithmetic mean roughness Sa and maximum height Sz, the thickness of the Li foil, arithmetic mean roughness Sa, maximum height Sz and development area ratio Sdr, and Li-Cu interface peel strength of the Li-Cu laminates 1 and 2 used in this example are shown in Table 1 below. The arithmetic mean roughness Sa and maximum height Sz of the Cu foil are values ​​of the surface on the Li foil side. The arithmetic mean roughness Sa, maximum height Sz and development area ratio Sdr of the Li foil are values ​​of the surface on the opposite side to the Cu foil side. In this example, the arithmetic mean roughness Sa, maximum height Sz and development area ratio Sdr were measured using a laser microscope (VK-X3000, manufactured by Keyence Corporation).

[0061] [Table 1]

[0062] In this example, three transfer materials, i.e., the unevenness transfer materials 1 to 3, were used as the unevenness transfer materials. The arithmetic mean roughness Sa, maximum height Sz thickness, and developed area ratio Sdr of the unevenness transfer materials 1 to 3 used in this example are shown in the following Table 2. All of the unevenness transfer materials 1 to 3 are made of electrolytic nickel foil.

[0063] [Table 2]

[0064] [Example 1] DME (1,2-dimethoxyethane) was dropped onto the surface of the Li layer of the Li-Cu laminate 1. Next, the surface of the Li layer of the Li-Cu laminate 1 and the uneven portion of the unevenness transfer material 2 were overlapped and sandwiched between 20 μm thick release copper foils to obtain an unevenness-forming laminate in which the release copper foil, the Li-Cu laminate 1, the unevenness transfer material 2, and the release copper foil were laminated in this order. The obtained unevenness-forming laminate was pressed with a linear pressure of 1 t / cm using a roll press so that the compression ratio was 45%. The release copper foil and the unevenness transfer material 2 were peeled off from the pressed unevenness-forming laminate to obtain an uneven Li-Cu laminate in which the unevenness was transferred to the surface of the Li layer.

[0065] [Examples 2 to 4, Comparative Examples 1 to 2] A Li-Cu laminate with projections and recesses was obtained in the same manner as in Example 1, except that the type of Li-Cu laminate, the type of solvent dropped onto the surface of the Li layer of the Li-Cu laminate, the type of projection and recess transfer material, and the compression ratio were changed as shown in Table 3 below.

[0066] [Comparative Example 3] The Li—Cu laminate 2 was used as the Li—Cu laminate of Comparative Example 3.

[0067] [Comparative Example 4] The Li-Cu laminate 2 was sandwiched between release copper foils to obtain a compression laminate in which the release copper foil, the Li-Cu laminate 2, and the release copper foil were laminated in this order. The obtained compression laminate was pressed with a linear pressure of 1 t / cm using a roll press so that the compression ratio was 41%. When the release copper foil was peeled off from the compression laminate after pressing, the Li foil was peeled off from the Cu foil of the Li-Cu laminate 2.

[0068] [Comparative Example 5] The Li—Cu laminate 1 was compressed in the same manner as in Comparative Example 4, except that the Li—Cu laminate 1 was used. The compressed Li—Cu laminate 1 was used as the Li—Cu laminate of Comparative Example 5.

[0069] [Table 3]

[0070] [evaluation] (1) Characteristics of the Li layer in Li-Cu laminates The arithmetic mean roughness Sa, maximum height Sz, developed area Sdr, O / C (oxygen / carbon) molar ratio, and Si / Li mass ratio of the Li layer were measured by the above-mentioned method for the uneven Li-Cu laminates obtained in Examples 1 to 4 and Comparative Examples 1 to 2, and the Li-Cu laminates of Comparative Examples 3 and 5. The arithmetic mean roughness Sa, maximum height Sz, and developed area ratio Sdr were measured using a laser microscope (VK-X3000, manufactured by Keyence Corporation). The O / C (oxygen / carbon) molar ratio was measured by using an XPS method to measure the molar ratio of carbon (C) and oxygen (O) within a range from the surface of the Li foil to a depth of 50 nm. The Si / Li mass ratio was calculated from the Si amount and Li amount of the uneven Li-Cu laminate. The Si amount and Li amount were obtained by dissolving the uneven Li-Cu laminate in acid and measuring the amounts of Si and Li in the obtained solution using an ICP emission spectrometer. The results are shown in Table 4 below.

[0071] (2) Characteristics of lithium metal secondary batteries (positive electrode) Acetylene black (AB) as an electron conductive material, polyvinylidene fluoride (PVDF) as a binder, and polyvinylpyrrolidone (PVP) as a dispersant were premixed with N-methyl-2-pyrrolidone (NMP) as a dispersion solvent, and wet-mixed in a planetary centrifugal mixer to obtain a premixed slurry. 0.8 Co 0.1 Mn 0.1 O2 (NCM811) and the obtained premixed slurry were mixed, and a dispersion process was performed using a planetary mixer to obtain a positive electrode paste. NCM811 has a median diameter of 12 μm. Next, the obtained positive electrode paste was applied to an aluminum positive electrode collector not having a primer layer, dried, pressed with a roll press, and then dried in a vacuum at 120 ° C. to form a positive electrode plate having a positive electrode active material layer. The obtained positive electrode plate was punched out to a size of 30 mm × 40 mm to form a positive electrode.

[0072] (Separator) The resin part was made of polyethylene (PE) with a thickness of 10 μm and a porosity of 45%, with a separator coated with 4 μm of ceramic on the surface facing the positive electrode.

[0073] (electrolyte) A solution of LiFSI [lithium bis(fluorosulfonyl)imide] in DME (1,2-dimethoxyethane) at a concentration of 2.5 mol / L was used.

[0074] (Preparation of lithium metal secondary batteries) An electrode laminate was obtained by laminating the above separator and the above positive electrode in this order on the Li layer of the uneven Li-Cu laminate obtained in Examples 1 to 4 and Comparative Examples 1 and 2, and the Li-Cu laminate in Comparative Examples 3 and 5. The obtained electrode laminate and the above electrolyte were placed in an exterior case, and the exterior case was sealed to produce a lithium metal secondary battery.

[0075] (Lithium metal secondary battery chemical formation process) The lithium metal secondary battery thus fabricated was held at a holding pressure of 50 kPa and allowed to stand at a temperature (25°C) for 24 hours. It was then charged at a constant current of 2.2 mA to 4.3 V, followed by a constant voltage charge at a voltage of 4.3 V for 1 hour, and then allowed to stand for 30 minutes, after which it was discharged at a constant current of 44 mA to 2.65 V. This charge / discharge cycle was repeated three times.

[0076] (Initial discharge capacity) The lithium metal secondary battery after the chemical formation process was left to stand for 1 hour at a holding pressure of 0.8 MPa and a temperature of (25°C). Next, constant current charging was performed at 14.5 mA up to 4.3 V, followed by constant voltage charging at a voltage of 4.3 V for 1 hour, and after leaving the battery to stand for 30 minutes, constant current discharging was performed at a current value of 14.5 mA up to 2.65 V, and the discharge capacity was taken as the initial discharge capacity (mAh). The results are shown in Table 4. In the following, the current value at which discharge can be completed in 1 hour for the initial discharge capacity obtained was taken as 1C.

[0077] (Initial internal resistance value) The lithium metal secondary battery after the initial discharge capacity measurement was left at a temperature (25°C) for 1 hour, then charged at 0.2C, and the charge level [SOC (State of Charge)] was adjusted to 50% and left to stand for 10 minutes. Next, the battery was pulse-discharged for 10 seconds at a C rate of 0.5C, and the voltage at 10 seconds of discharge was measured. Then, the voltage at 10 seconds of discharge was plotted against the current at 0.5C, with the horizontal axis representing the current value and the vertical axis representing the voltage. Next, after leaving the battery to stand for 10 minutes, the battery was supplementarily charged to return the SOC to 50%, and then left to stand for another 10 minutes. The above operation was performed for each C rate of 1.0C, 1.5C, 2.0C, 2.5C, and 3.0C, and the voltage at 10 seconds of discharge against the current value at each C rate was plotted. Then, the slope of the approximation line obtained from each plot by the least squares method was calculated as the internal resistance value (Ω·cm) of the lithium ion secondary battery obtained in this example. 2 The results are shown in Table 4.

[0078] (High-rate charge / discharge cycle test) The battery was charged at a constant current of 74 mA up to 3.823 V, then at 52 mA up to 4.051 V. It was then charged at a constant current of 46 mA up to 4.173 V, and then at 22 mA up to 4.3 V. It was then charged at CV to 4.3 V for 90 minutes. Discharge was performed at a constant current of 18 mA down to 2.65 V. This was repeated 48 times. Table 4 shows the discharge capacity at the 2nd cycle, the discharge capacity at the 48th cycle, and the ratio of the discharge capacity at the 48th cycle to the discharge capacity at the 2nd cycle (discharge capacity retention rate).

[0079] (Internal resistance after cycle testing) The lithium metal secondary battery after the high-rate charge-discharge cycle test was charged at a constant current of 14.5 mA to 4.3 V, then charged at a constant voltage of 4.3 V for 1 hour, allowed to stand for 30 minutes, and discharged at a constant current of 14.5 mA to 2.65 V for two cycles. The internal resistance of the lithium metal secondary battery after two cycles was measured in the same manner as the initial internal resistance. The obtained internal resistance was used as the internal resistance after the cycle test, and the ratio (variation rate) of the internal resistance after the cycle test to the initial internal resistance was calculated. The results are shown in Table 4.

[0080] [Table 4]

[0081] The lithium metal secondary battery using the uneven Li-Cu laminate obtained in Examples 1 to 4 as the negative electrode has a high discharge capacity and a high discharge capacity retention rate at the 48th cycle of the high-rate charge-discharge cycle test, and a small variation rate of the internal resistance value due to the high-rate charge-discharge cycle test. From this result, it can be seen that the lithium metal secondary battery using the uneven Li-Cu laminate obtained in Examples 1 to 4 as the negative electrode has a high capacity and is excellent in rate characteristics and cycle characteristics. In contrast, the lithium metal secondary battery using the uneven Li-Cu laminate of Comparative Examples 1 and 2 and the Li-Cu laminate of Comparative Example 3 has a low discharge capacity and a low discharge capacity retention rate at the 48th cycle of the high-rate charge-discharge cycle test, and a large variation rate of the internal resistance value due to the high-rate charge-discharge cycle test. The poor characteristics of the high-rate charge-discharge cycle test of Comparative Example 1 are believed to be due to the fact that the uneven Li-Cu laminate of Comparative Example 1 has a small development area ratio Sdr and a small reaction area. The reason why the characteristics of the high-rate charge-discharge cycle test of Comparative Example 2 are inferior is considered to be because the Li-Cu laminate with projections and recesses of Comparative Example 2 has a large O / C molar ratio, so that the surface is oxidized to generate components such as LiOH and Li2O, making it difficult for lithium ions to deposit uniformly during charging. The reason why the characteristics of the high-rate charge-discharge cycle test of Comparative Example 3 are inferior is considered to be because the Li-Cu laminate of Comparative Example 3 does not have projections and recesses on its surface, so that the reaction area is small. Comparative Example 5 could not be charged up to 4.3V in the chemical formation process of the lithium metal secondary battery. This is considered to be because the Li layer of the Li-Cu laminate of Comparative Example 5 does not have projections and recesses on its surface, so that the O / C molar ratio is large, so that lithium ions deposit non-uniformly during charging, causing an internal short circuit. [Explanation of symbols]

[0082] 10 Lithium metal secondary battery 20 negative electrode 20a Negative electrode material laminate 21, 21a Negative electrode current collector 22, 22a Lithium-containing metal layer 30 Separator 40 positive electrode 41 Positive electrode current collector 42 Positive electrode active material layer 100 Manufacturing equipment 110 Roll Press 120 Laminate for forming unevenness 121 Release plate 122 Textured transfer material

Claims

1. A negative electrode current collector and a lithium-containing metal layer disposed on at least one surface of the negative electrode current collector, a lithium-containing metal layer having a surface with a concave-convex shape, a developed area ratio Sdr of the surface being 1.0 or more, and the surface being covered with an oxidation-preventing coating;

2. 2. The negative electrode for a lithium metal secondary battery according to claim 1, wherein the arithmetic mean roughness Sa of the surface of the lithium-containing metal layer is 0.5 μm or more.

3. 2. The negative electrode for a lithium metal secondary battery according to claim 1, wherein the antioxidant coating contains oxygen and carbon, and an average content of the oxygen relative to an average content of the carbon within a range from a surface of the antioxidant coating to a depth of 50 nm is in a molar ratio of 3 or more and 5 or less.

4. 2. The negative electrode for a lithium metal secondary battery according to claim 1, wherein the antioxidant coating comprises lithium carbonate.

5. 2. The negative electrode for a lithium metal secondary battery according to claim 1, wherein the lithium-containing metal layer has a silicon content of 400 mass ppm or less relative to the lithium content.

6. 2. The negative electrode for a lithium metal secondary battery according to claim 1, wherein a peel strength between the negative electrode current collector and the lithium-containing metal layer is 100 N / cm or more.

7. A lithium metal secondary battery comprising the negative electrode for lithium metal secondary batteries according to any one of claims 1 to 6.

8. A preparation step of preparing a laminate having a negative electrode current collector and a lithium-containing metal layer disposed on at least one surface of the negative electrode current collector; and a concave-convex transfer step of pressing a concave-convex transfer material having a concave-convex portion with a developed area ratio Sdr of 1.0 or more onto the surface of the laminate on the lithium-containing metal layer side.

9. 9. The method for producing a negative electrode for a lithium metal secondary battery according to claim 8, wherein in the unevenness transfer step, a solvent having an ether bond or a carbonate bond is interposed between the surface of the laminate on the lithium-containing metal layer side and the unevenness transfer material.

10. The method for producing a negative electrode for a lithium metal secondary battery according to claim 8 , wherein the surface of the unevenness transfer material has an arithmetic mean roughness Sa of 0.5 μm or more.

Citation Information

Patent Citations

  • Anode active material for lithium ion secondary battery, anode using the same, and lithium ion secondary battery

    JP2012178299A

  • Lithium ion secondary battery anode and lithium ion secondary battery using the same

    JP2012178309A

  • Lithium electrode and lithium secondary battery including the same

    JP2020523751A

  • Manufacture of metallic current collector

    JP1995272726A